A Mixture of D-Amino Acids Enhances the Biocidal Efficacy of CMIT/MIT Against Corrosive Vibrio harveyi Biofilm - Liu, Xiaomeng; Li, Zhong; Fan, Yongqiang; Lekbach, Yassir; Song, Yongbo; Xu, Dake; Zhang, Zhichao; Ding, Lei; Wang, Fuhui (Frontiers in Microbiology, 2020)
Biocides are widely used for the mitigation of microbial contamination, especially in the field of the aviation fuel industry. However, the long-term use of biocide has raised the concerns regarding the environmental contamination and microbial drug resistance. In this study, the effect of a mixture of D-amino acids (D-tyrosine and D-methionine) on the enhancement of the bactericidal effect of 5-Chloro-2-Methyl-4-isothiazolin-3-one/2-Methyl-2H-isothiazole-3-one (CMIT/MIT) against corrosive Vibrio harveyi biofilm was evaluated. The results revealed that D-Tyr and D-Met alone can enhance the biocidal efficacy of CMIT/MIT, while the treatment of 5 ppm CMIT/MIT, 1 ppm D-Tyr and 100 ppm D-Met showed the best efficacy comparable to that of 25 ppm CMIT/MIT alone. The triple combination treatment successfully prevented the establishment of the corrosive V. harveyi biofilm and effectively removed the mature V. harveyi biofilm. These conclusions were confirmed by the results of sessile cell counts, images obtained by scanning electron microscope and confocal laser scanning microscope, and the ATP test kit.